Analysis of Risk Factors for Death of Covid-19 Patients at Undata Hospital Palu - Nur Afni; Sri Rahayu (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2022)
Patients with comorbid are above 45 years on average. Diabetes and heart disease are risk factors for death from COVID-19 because those with diabetes have a 4.384 times greater risk of dying from Covid-19 than patients without diabetes. Patients with heart disease have a 4.319 times greater risk of dying from Covid -19 of the patients without comorbidities. This research aims to determine the risk factors for death of COVID-19 patients at Undata Hospital Palu. This is an analytical survey research with case control study method. The total sample is 62 samples consisting of 31 cases and 31 controls using the statistical test, namely the Odds Ratio. The results show that age is a risk factor with an OR value of 5.975>1, gender is a risk factor with an OR value of 1.304>1 and comorbidities are a risk factor with an OR value of 11.979 > 1. For Undata Hospital, it is expected to further improve the quality of Covid services, especially for patients who have age and comorbid risks so as to speed up the healing process of COVID-19 patients and reduce the death rate due to Covid-19.